Rancang Bangun Sistem Informasi Approval Dismentling NTE Telkom Akses dengan Metode RAD (Rapid Application Development) - Aditya Pratama Simanungkalit; Nadya Andhika Putri; Virdyra Tasril (PT. INOVASI TEKNOLOGI KOMPUTER, 2023)
This study aims to develop a web-based Information System for Approval Dismentling NTE using the RAD (Rapid Application Development) method at PT Telkom Akses. The system design process is carried out using DFD (Data Flow Diagram) to determine the necessary design steps. The system development involves programming languages such as PHP, HTML, JavaScript, and CSS, along with a SQL database for data storage. The RAD method is utilized in the design phase, which consists of three main steps: planning, design, and implementation. The research findings indicate that the web-based Information System for Approval Dismentling NTE has no significant impact on the performance of asset monitoring at PT Telkom Akses. Despite PT Telkom Akses having its own Approval system application, there are still several shortcomings, including an unattractive interface. This study contributes to the development of a web-based Information System for Approval Dismentling NTE using the RAD method. The implementation of this system is expected to enhance the efficiency and effectiveness of the NTE dismentling approval process at PT.Telkom Akses. Improvements that can be made to the system include refining the interface to make it more appealing and addressing other existing deficiencies.